Proses Penyelesaian Perkara Waris Terhadap Pembagian Harta Warisan (Study Kasus di Pengadilan Negeri Klaten) - Basri, Hasan (2016)
This study aims to determine the consideration of judges in determining the evidentiary heirs receive inheritance rights, the division of inheritance. To determine the consideration as well as the judge in determining the verdict of the rights in the can by the heir in the division of inheritance. The method I use is a normative juridical approach. In the preparation of this paper, the author uses descriptive research. Using this type of primary data and secondary data. Data collection techniques used through library research and field research. Analysis that the authors use in this study is qualitative data analysis documentation, Based on the results of research and discussion, it can be concluded that the settlement of inheritance to the division of inheritance resolved through the courts, where the litigants domiciled in Klaten, the case resolved in District Court Klaten. As in the decision No. No. 71 / PDT.G / 2011 / PN.Klt mentioned that judges decide on the basis of the provisions of Section 852 Code of Civil Law that goods such as land disputes yard and house, originally a relics of the late Mr. Karto Wiredjo and then in inheritance by mBok Kartowiredjo called Poniyem should be divided by five (5) equally.